Implementasi Sistem Informasi Akuntansi dalam Mendukung Efisiensi Operasional Perusahaan pada PT Industri Jamu dan Farmasi Sido Muncul Tbk di Indonesia - Lediyajaya Lediyajaya; Meisyah Rahel Gracella; Helmi Herawati (AKUNTANSI 45, 2026)
This community service research focuses on examining how Accounting Information Systems (AIS) are utilized to enhance operational efficiency at PT Industri Jamu dan Farmasi Sidomuncul Tbk. A descriptive qualitative method is employed for this research, utilizing data gathering techniques such as direct observation, detailed interviews, and the study of existing documentation. The findings indicate that the AIS used by Sidomuncul has effectively brought together various accounting tasks, including recording transactions, managing inventory, and providing real-time financial reports. The use of AIS has demonstrated a significant boost in the company's operational efficiency, highlighted by a 60% decrease in the time taken for data processing, a reduction in recording mistakes, and a faster pace of managerial decision-making. Moreover, the introduction of AIS has enhanced data security, improved transparency, and fostered better collaboration among different departments within the organization. Consequently, AIS stands out as a vital tool for promoting sustainable business performance and competitiveness in the pharmaceutical sector. This study suggests that the company should continually update its systems and enhance human resource capabilities in managing AIS to maximize its advantages.